Some remarks about equilibrium points in n-person non-coalition games - Vilkas, E. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Э. И. Вилкас. Несколько замечаний о ситуациях равновесия бескоалиционной игры многих лицE. Vilkas. Keletas pastabų apie nekoalicinių daugelio asmenų lošimų pusiausvyros situacijas